The The role of family environment and learning motivation in the dropout phenomenon among students in Eastern Indonesia border regions - Hernawati, Retno; Panie, Maria Yuliana; Neonufa, Samrid; Tajuddin, Al Ihzan (Privietlab, 2025)
This study examines the role of learning motivation as a mediating variable in the relationship between the family environment and the phenomenon of school dropout in the Indonesian-Timor Leste border area. A quantitative approach was used as the explanatory research method. The population in this study comprised high school/vocational school students who dropped out of school in the Malacca Regency, East Nusa Tenggara. A sample of 120 respondents from 12 sub-districts was obtained through proportional sampling techniques. Data collection was carried out through questionnaires and data analysis using Path Analysis with the help of the SPSS 27. The results showed that family environment had a significant effect on learning motivation, with a score of 9.676 and a significance value of 0.001. Family environment had a significant effect on school dropouts, which was calculated to be 4.312 and a significance value of 0.001. Learning motivation had a significant effect on school dropouts, with a score of 4.465 and significance value of 0.001. Learning motivation was able to mediate the influence of the family environment on school dropouts, with an indirect effect of -1,048, and the Sobel test score = 12,467 > t table = 1,658; thus, the mediation was significant. This study concluded that a positive family environment can increase learning motivation and indirectly reduce the risk of dropping out of school. These findings have important implications for education policies in border areas.